Announcement Of Reduction In BI7DRR Interest Rate For 2019 To 2021 On Abnormal Return And Cumulative Abnormal Return Of Indonesian Banking Share - Deswita Murdiana; Fajri Adrianto; Mohamad Fany Alfarisi (Institute of Computer Science (IOCS), 2022)
This study aims to determine the significant positive abnormal return on Indonesian banking stocks during the announcement of the BI7DRR interest rate cut, to determine the difference between average abnormal returns and cumulative abnormal returns in Indonesian banking stocks before and after the announcement of the BI7DRR interest rate cut in 2019 to 2021. The study This is an event study of 10 announcement dates with an event period of 12 days, namely -5, event date, +5. The sample used is 22 banking companies selected using purposive sampling technique. This study used One Sample t-Test, Paired Samples t-Test, Wilcoxon One Sample and Wilcoxon Paired Samples. The results show that firstly, there was a significant positive abnormal return in Indonesian banking stocks when the announcement of the BI7DRR interest rate cut on 17-18 July 2019 (2nd event date) had Event Study, BI7DRR Interest Rate Reduction,Abnormal Return, Cumulative Abnormal Return a significant value of 0.006 or 0.6%, 19-20 February 2020 (event date). 1) significant value 0.012 or 1.2%, June 17-18 2020 (2nd event date) significant value 0.014 or 1.4% and July 15-16 2020 (2nd event date) significant value 0.016 or 1.6%. Second, there was no abnormal return on Indonesian banking stocks which was significantly positive when the BI7DRR interest rate cut was announced on 21-22 August 2019, 18-19 September 2019, 23-24 October 2019, 18-19 March 2020, 18-19 November 2020 and 17-18 February 2021. Third, there are differences before and after the announcement of the BI7DRR interest rate cut by showing the results of significant average abnormal returns & cumulative abnormal returns on 18-19 September 2019 a significant value of 0.012 or 1.2%, 19-20 February 2020 significant value is 0.0001 or 0.01% and on 17-18 February 2021 the significant value is 0.013 or 1.3%. Fourth, there is no difference in average abnormal returns & cumulative abnormal returns before and after the announcement of BI7DRR Interest Rate reduction on 17-18 July 2019 significant value of 0.069 or 6.9%, 21-22 August 2019 significant value of 0.115 or 11.5%, 23-24 October 2019 significant value 0.685 or 68.5%, March 18-19 2020 significant value 0.372 or 37.2%, June 17-18 2020 significant value 0.390 or 39%, July 15-16 2020 significant value 0.091 or 9.1%, and 18-19 November 2020 significant value 0.610 or 61%.